2015
DOI: 10.3389/fgene.2015.00046
|View full text |Cite
|
Sign up to set email alerts
|

CHRNA4 rs1044396 is associated with smoking cessation in varenicline therapy

Abstract: Background: The large individual variability in response to drugs for smoking cessation suggests that specific treatments can be more effective in particular subgroups of smokers. In the context of personalized medicine, the main aim of the present study was to evaluate whether the CHRNA4 and CHRNB2 polymorphisms are associated with response to smoking cessation therapies in patients from a smoker assistance program.Methods: This cohort study enrolled 483 smoking patients who received behavioral counseling and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 47 publications
(84 reference statements)
1
14
0
1
Order By: Relevance
“…Many studies have identified the association of polymorphisms in the CHRNA5-A3-B4 gene with smoking cessation in response to smoking cessation therapies [ 2 , 29 31 ]. Recently, our group of researchers found the association of the CHRNA4 rs10443196 and cytochrome P450 2B6 ( CYP2B6) 785A > G polymorphisms with a higher success rate in varenicline and bupropion treatment, respectively [ 32 , 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have identified the association of polymorphisms in the CHRNA5-A3-B4 gene with smoking cessation in response to smoking cessation therapies [ 2 , 29 31 ]. Recently, our group of researchers found the association of the CHRNA4 rs10443196 and cytochrome P450 2B6 ( CYP2B6) 785A > G polymorphisms with a higher success rate in varenicline and bupropion treatment, respectively [ 32 , 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…The present study identified the influence of the gene coding for the alpha4 subunit of the nicotinic acetylcholine receptor ( CHRNA4 ) on IGD. With respect to addiction, a biological link between CHRNA4 and the nicotine-addiction phenotype has been established [ 21 , 49 51 ]. Knock-in mice with a point mutation in the CHRNA4 gene showed reduced nigrostriatal dopaminergic function [ 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…To address this assumption, the present study conducted two case-control studies of IGD and AD using the same candidate genes, but the results do not support the assumption. Although rs1044396 of the CHRNA4 gene was associated with nicotine addiction and the addiction phenotype [ 21 , 49 51 , 55 ], further association, family-aggregation, or twin studies are needed to examine the extent to which IGD shares a common genetic vulnerability with substance addictions.…”
Section: Discussionmentioning
confidence: 99%
“…Tobacco dependence does not just mean physical dependence, it also means psychological dependence . Previous studies revealed genetic, individual, and psychological factors significantly contribute to smoking behavior . A solid body of evidence showed that nicotine, the major addictive component of tobacco, induces continuous tobacco use and dependence .…”
Section: Introductionmentioning
confidence: 99%
“…Nicotine initiates its effects by binding to nicotinic acetylcholine receptors (nAChRs) that were coded by nicotinic acetylcholine receptor genes (CHRN). Single nucleotide polymorphisms (SNPs) in CHRNA3‐CHRNA5‐CHRNB4, CHRNA4‐CHRNB2, and CHRNA6‐CHRNB3 have been found to be related to SC. However, these articles only investigated the relationships between single SNP in CHRN genes and SC, which results in two possible limitations.…”
Section: Introductionmentioning
confidence: 99%